2013
DOI: 10.5152/jtgga.2013.53323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Follicular Fluid NO, MDA and GSH Levels on in vitro Fertilization Outcomes

Abstract: Objective:To investigate the biochemical markers such as nitric oxide (NO), malondialdehyde (MDA) and reduced glutathione (GSH), indicators of the oxidative status of the follicle, to predict the outcome of in vitro fertilization. Material and Methods: Follicular aspirates of dominant follicleswere collected during oocyte retrieval. Biochemical analyses of NO, MDA and GSH were performed on all aspirates. Results:When the successful and unsuccessful pregnancy groups were compared in terms of NO, MDA and GSH, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…However, while both Oral et al [8] and Jozwick et al [9] found no significant correlation between IVF outcome and ROS markers, Das et al [10] demonstrated a negative correlation between ROS levels and embryo quality. Moreover, Yalç ınkaya et al [11] found significantly higher intra-follicular NO levels in the non-pregnant group compared to the pregnant group, which did not correlate to other IVF cycle variables, such as, the number of mature oocytes, fertilization rate, or embryo grading. Of notice, none of the aforementioned studies have followed the outcome of a single oocyte and related it to its own FF/microenvironment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, while both Oral et al [8] and Jozwick et al [9] found no significant correlation between IVF outcome and ROS markers, Das et al [10] demonstrated a negative correlation between ROS levels and embryo quality. Moreover, Yalç ınkaya et al [11] found significantly higher intra-follicular NO levels in the non-pregnant group compared to the pregnant group, which did not correlate to other IVF cycle variables, such as, the number of mature oocytes, fertilization rate, or embryo grading. Of notice, none of the aforementioned studies have followed the outcome of a single oocyte and related it to its own FF/microenvironment.…”
Section: Discussionmentioning
confidence: 95%
“…While several studies reported a positive correlation between FF ROS level and pregnancy rate following an IVF treatment [6,7], others found either no correlation [8,9], or demonstrated a negative correlation between ROS levels and reproductive functions [10][11][12]. We believe that this inconsistency derived from the different study methodology, which examine ROS from different FF sources, i.e.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, one of the major objectives of the present study was to determine the influences of melatonin on the oxidative status of pre-ovulatory follicles by measuring the levels of MDA, a reliable marker of intra-cellular stress (Parlakpinar et al 2013), as well as the levels of different antioxidants in the same ovarian follicular extracts of the experimental carp. A high MDA level denoted an elevated oxidative stress (Yalçınkaya et al 2013) in the pre-ovulatory follicles of the control fish. On the other hand, a significant reduction in the level of MDA and the stimulation of enzymatic (SOD, CAT, GPx, GRd and GST) as well as Melatonin and ovaprim actions on carp oocytes non-enzymatic (GSH) antioxidants in the follicular extracts of the melatonin-treated carp collectively demonstrated antioxidative actions of melatonin in the pre-ovulatory follicles of the concerned fish.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important harmful effects of free radical attack is the oxidation of unsaturated fatty acids, known as lipid peroxidation. MDA, one of the typical end products of lipid peroxidation, can be used as a cumulative measure of lipid peroxidation [32]. SOD, one of important endogenous antioxidants, protecting cells exposed to oxygen.…”
Section: Discussionmentioning
confidence: 99%